ARE PREHOSPITAL TREATMENT OR CONVEYANCE DECISIONS AFFECTED BY AN AMBULANCE CREW'S ABILITY TO ACCESS A PATIENT'S HEALTH INFORMATION? A UK SURVEY. Issue 6 (19th May 2015) - Zorab, Ollie; Robinson, Maria; Endacott, Ruth
Abstract : Background: A shift from a predominantly emergency service, towards one where a wide range of conditions are managed and treated on scene presents numerous challenges for ambulance services and clinicians. The effective management of a broad range of patients and conditions in the ambulance setting will have an impact on other parts of the health service including emergency departments and primary care. Methods: A two part online survey was distributed to operational staff working for a regional UK ambulance service. Clinicians were asked to report their experiences of accessing patient information and making decisions about patient management based on four hypothetical patient scenarios. Results: A survey of clinical staff (n=302) revealed that overall, 285 (94.4%) of respondents felt that they had been unable to access health information about a patient that they were caring for, whilst 274 (90.7%) felt that this lack of information had led to a less appropriate care pathway being selected and the majority (246/81.5%) felt that information was easier to access during working hours on weekdays. Sources that respondents use when trying to access a patient's health information were mainly the patient's General Practitioner (n=294, 94.7%). Hospital Discharge and GP Summaries were the two pieces of information which respondents considered as helpful sources of information. Conclusions: Decisions regarding the most appropriate care for patients presenting to the ambulance service are best informed by access to accurate and complete health information and records. An understanding of patients' pre-existing medical conditions, recent treatments and health information is needed for the selection of the most appropriate care; this information is often difficult to obtain in the ambulance service setting.